Implementation Of Critical Path Method And Critical Chain Project Management For Project Schedulling: Penerapan Metode Jalur Kritis Dan Manajemen Proyek Rantai Kritis Untuk Penjadwalan Proyek - Mukandar Idris; Mega Cattleya Prameswari Annissa Islami (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Work time scheduling is a crucial factor that affects the success of construction project implementation. Project management is a discipline that utilizes information, skills, tools, and procedures to plan, organize, and direct resources (human, time, financial, and material) to achieve set goals within a certain period of time. The use of scheduling programs or tools increases the effectiveness and efficiency of project management. This study aims to implement the Critical Path Method (CPM) and Critical Chain Project Management (CCPM) techniques for work duration scheduling on the oil tank foundation construction project at PT XYZ. The study data were obtained by analyzing the correlation between the relationship between work and the duration of each activity. The results of the comparative analysis of the two methodologies were used to identify important tasks and ensure the ideal project duration. The results of the analysis showed that the CCPM duration was 90 days, 8 days faster than the CPM approach. PT XYZ is advised to use an application-based scheduling method to improve the effectiveness and efficiency of its project implementation.